PENGARUH PROMOSI, HARGA DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT (Studi Kasus: Pengguna Sepeda Motor Honda Beat Pada Masyarakat Kecamatan Medan Tembung) - Simanihuruk, Peran (Jurnal Manajemen dan Bisnis, 2019)
The purpose of the study was to analyze the effect of promotion, price and product design partially and simultaneously on purchasing decisions and analyze the dominant influence of the three variables on the purchase decisions of Honda Beat motorbikes. Benefits of Research, for companies providing empirical evidence regarding the effect of promotion, price and design on purchasing decisions and providing solutions in the form of suggestions on the management of these variables. The number of samples is 96 respondents, questionnaire data collection methods and documentation, Techniques of multiple linear regression data analysis. The results showed: Y = 2,711 + 0,268X1 + 0,227X2 + 0,335X3, meaning that promotion, price and product design had a positive influence on purchasing decisions of Honda Beat motorbikes in Medan Tembung Subdistrict. With the t test and the F test the three independent variables have a positive and significant influence partially and simultaneously on purchasing decisions. Based on the magnitude of the regression coefficients, it turns out that the three variables that have the dominant influence on purchasing decisions are product design variables. So it is hoped that the Company will be able to maintain and improve the competitiveness of its products, affordable prices, innovative Honda product designs.